3D printers - Murray, Julie, 1969- (2021)
Technology keeps progressing and advancements in 3D printers will continue to amaze mankind for years to come. Readers will learn about amazing inventions throughout the years, what they do, why they're important, and what technology of the future might look like. This title is at a Level 3 and is specifically written for transitional readers. Aligned to Common Core Standards and correlated to state standards
Ages 5-9
Keywords: Computer printers -- Juvenile literature; Three-dimensional imaging -- Juvenile literature; Three-dimensional printing -- Juvenile literature; Computer printers; Three-dimensional imaging; Three-dimensional printing; Juvenile works